Changes in central bank procedures during the subprime crisis and their repercussions on monetary theory - Marc Lavoie (Levy Economics Institute of Bard College, 2010)
The subprime financial crisis has forced several North American and European central banks to take extraordinary measures and to modify some of their operational procedures. These changes have made even clearer the deficiencies and lack of realism in mainstream monetary theory, as can be found in both undergraduate textbooks and most macroeconomic models. They have also forced monetary authorities to reject publicly some of the assumptions and key features of mainstream monetary theory, fearing that, on that mistaken basis, actors in the financial markets would misrepresent and misjudge the consequences of the actions taken by the monetary authorities. These changes in operational procedures also have some implications for heterodox monetary theory; in particular, for post-Keynesian theory. The objective of this paper is to analyze the implications of these changes in operational procedures for our understanding of monetary theory. The evolution of the operating procedures of the Federal Reserve since August 2007 is taken as an exemplar. The American case is particularly interesting, both because it was at the center of the financial crisis and because the U.S. monetary system and its federal funds rate market are the main sources of theorizing in monetary economics.
Keywords: E42; E43; E58; 330; federal funds rate; corridor system; interest on bank reserves; money multiplier; Geldtheorie; Postkeynesianismus; Zinspolitik; Transmissionsmechanismus; Finanzmarktkrise; USA